Effect of copper and zinc as a supplement fertilizer on growth of radish (Raphanus sativus) root and foliage (Current Horticulture, 2024)
The foliar spray of copper (0.3%) and znc (0.4%) solution at 15 and 25 days of growth improved the plant height, fresh weight and root  size of radish (Raphanus sativus L.). The application of copper and zinc along with N, P, K fertilizers improved crop growth more than  the control. The concentration of 0.6% copper and 0.8% sinc showed some toxic effect and reduced growth of leaves and root but was  better than the no application of Cu and Zn elements.
Keywords: Copper; Zinc; growth; toxic; vitamins